2021
DOI: 10.1111/fcsr.12400
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Financial Education Sources on Emergency Savings: The Role of Financial Literacy

Abstract: Using data from the 2018 National Financial Capability Study, this research explored the relationship between financial education sources and emergency savings of U.S. adults, and examined the mediating role of financial literacy. The results showed that receiving financial education from both school and workplace had positive associations with having emergency funds. Financial literacy was found to be positively associated with having emergency funds and financial literacy mediated the relationship between fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…This paper examined the relationship between education and financial literacy and the mediating role of financial literacy in linking education to financial decision-making. The literature indicated that formal education can promote financial education, and financial literacy mediates the relationship between financial education and financial decisionmaking (Fan and Zhang, 2021). Education also has a direct impact on financial market PAR 36,1 participation, and financial literacy mediated this relationship (Inkmann et al, 2011).…”
Section: Mediating Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper examined the relationship between education and financial literacy and the mediating role of financial literacy in linking education to financial decision-making. The literature indicated that formal education can promote financial education, and financial literacy mediates the relationship between financial education and financial decisionmaking (Fan and Zhang, 2021). Education also has a direct impact on financial market PAR 36,1 participation, and financial literacy mediated this relationship (Inkmann et al, 2011).…”
Section: Mediating Effectmentioning
confidence: 99%
“…Second, although education and financial literacy have received much attention in research on household financial behavior, their impact on commercial insurance has not been explored in depth, which was the major aim of this study. Third, although the mediating effect of financial literacy between financial education and financial behavior has been occasionally studied (Son and Park, 2019; Carpena and Zia, 2020; Fan and Zhang, 2021), the mediating effect of financial literacy between education and financial behavior has been occasionally studied (Son and Park, 2019; Carpena and Zia, 2020; Fan and Zhang, 2021), yet the mediating effect of financial literacy between education and financial behavior including commercial insurance purchase is rare. Literature shows that formal education affects financial literacy and commercial insurance purchase (Ankrah Twumasi et al , 2021; Li et al , 2021), and financial literacy impacts commercial insurance purchase (Liu et al , 2023; Duan et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chowdhry and Dholakia (2020) and Middlewood et al (2018) find that financial literacy strengthens the relationship between financial self‐awareness and the propensity to save and invest. Fan and Zhang (2021) show that financial literacy is positively related to having emergency funds and also mediates the relationship between financial education and emergency savings. Sekita et al (2022) find that financial literacy has an economically large and positive impact on wealth accumulation.…”
Section: Literature and Motivationmentioning
confidence: 99%
“…Understanding leadership characteristics specific to the small retailer provides insights and builds a deeper understanding of these leaders. Fan and Zhan ( 2020 ) stress the recent and urgent need to be equipped for the COVID‐19 disaster. Therefore, this study explores small retail business responses as the COVID‐19 pandemic crisis unfolds and it provides discovery of small retail business leaders’ actions taken during business uncertainty.…”
Section: Introductionmentioning
confidence: 99%